Culture-led regeneration for urban spaces - Sposito, Sabrina (Urbani izziv, 2018)
Wide areas in urban peripheries are made up of the council housing, i.e., neighbourhoods provided by public authorities. Diverse in building forms and types, these areas are frequently equipped with large open spaces: their "public" dimension, in physical and social terms, which is currently in crisis. The aim of this article is to discuss two issues arising from this fact: how the sharing of food-related processes can have a strategic role in the redevelopment of the "public city", and how the "implicit planning of these processes may provide useful insights to update planning tools and define new types of public spaces. A multiplicity of reflections leads to the conclusion that public spaces have declined, primarily, due to their inability to represent an increasingly fragmented and diverse society. In this respect, food recreates the primaeval sense of sharing, which encourages new forms of self-promoted public spaces. An innovation of these spaces can be found in the ability to activate or enhance not only social but also economic and cohesive social relationship networks that can break down the mechanisms leading to isolation, closures and marginality often affecting peripheral council housing neighbourhoods.
Keywords: council housing; creative practices; food providing and distribution; food spaces; javni prostori; kreativne prakse; public city; urban regeneration; urbana regeneracija